The Effect of Teaching Model for Hot Conceptual Change (TMHCC) for Promoting 11th Grade Students’ Argumentation Skills and Conceptual Chemistry on Chemical Equilibrium: - - Jaithawin, Worawat; Dokmai, Panwilai (Ratchaphruek Journal, 2021)
The purposes of this research wereto study 1) the students’ conceptual understanding of chemical equilibrium after learning with a teaching for conceptual change (TMHCC) of Kural and Kocakulah, and 2) the students’ argumentation skills after learning with a teaching for conceptual change (TMHCC) of Kural and Kocakulah. The target group was 39 of 11-grade students in a large sizeschool. The research tools were 1) ninelesson plans for teaching conceptual change of Kural and Kocakulah with 14 hours of teaching time, and 2) ninemainconcepts of two tires conceptual test on chemical equilibrium; Part 1: a four- multiple choices, and Part 2: a rationale writing, and 3) two issues of open-ended argumentation skills test, 6 questions each, totally 12 questions. The data analysis statistics were mean, standard deviation and percentage. The research results revealed that 1) most students hold conceptual understanding of Sound Understanding (SU = 41.60%) and Partial Understanding (PU = 48.72%) and some hold PU with Specific Alternative Conception (PUSAC = 9.69), 2) The students had post-average score on argument skills higher than the pre-average score in all areas and most of them were at level 3 of argumentation skills, they could identify only 3 out of 6 elements of argumentation skills.